14-3-3 protein sigma isoform co-localizes with phosphorylated α-synuclein in Lewy bodies and Lewy neurites in patients with Lewy body disease. (1st May 2018) - Wakabayashi, Kaori; Umahara, Takahiko; Hirokawa, Katsuiku; Hanyu, Haruo; Uchihara, Toshiki
Highlights: Localization of 14-3-3 sigma isoform was examined in brain tissue with Lewy body disease. Lewy bodies and Lewy neurites are positive for the sigma isoform. Sigma isoform co-localizes with α-synuclein in Lewy bodies and Lewy neurites. Abstract: α-Synuclein shares structural homology with 14-3-3 proteins. Seven 14-3-3 protein isoforms have been identified in mammals. Among them, the 14-3-3 sigma isoform was initially considered absent in the mammalian brain. However, we previously identified immunohistochemical association of 14-3-3 sigma with Pick bodies. Because 14-3-3 isoforms other than sigma isoform have been identified in Lewy bodies, we were prompted to look for this 14-3-3 sigma-like immunoreactivity (IR) in Lewy bodies in the brainstem, cerebral cortex, and Lewy neurites in seven patients with Lewy body disease. Unexpectedly, 14-3-3 sigma-like IR was consistently found in various types of Lewy pathologies in all cases examined. Double labeling studies confirmed its colocalization with alpha-synuclein. In general, 14-3-3 proteins can trap and hold some phosphorylated proteins in the cytoplasm and they can prevent or mediate apoptosis and survival of some cells. More precisely, the 14-3-3 sigma isoform is unique in its multiple cellular functions such as facilitating cell cycle arrest in the G2 phase, positively regulating p53, and suppressing tumor growth. Although the precise role of 14-3-3 sigma in the development of Lewy pathology remains elusive, its consistent association to Lewy pathology may expand our understanding of Lewy pathogenesis.